Quality of Life of Patients with Prostate Adenoma: Before and After Surgery - Nishonbaev Rasulzhon Ravshanbek ugli,; Davronov Bakhodirjon Abdirahim ugli, (American Journal of Biomedicine and Pharmacy, 2025)
Benign prostatic hyperplasia (BPH), or prostate adenoma, is one of the most common urological pathologies in men over 50 years of age. It affects the quality of life of patients, causing symptoms such as frequent and painful urination, sleep disorders, decreased sexual activity, and general weakness. Surgical intervention is one of the main methods of treating BPH. The purpose of this study is to assess changes in the quality of life of patients before and after surgery, as well as to identify factors affecting treatment outcomes. The study involved 100 patients of the urological clinic in Ferghana who underwent transurethral resection of the prostate (TURP). The quality of life was assessed using the IPSS and SF-36 scales. The results showed a significant improvement in the quality of life after surgery, especially with regard to lower urinary tract symptoms and general physical activity.